Peningkatan Kompetensi Keterampilan Peserta Didik dalam Pembelajaran Cerita Pendek - Neny Handayani (Jurnal Bintang Pendidikan Indonesia, 2024)
Before a teacher uses a test, the teacher should first measure the degree of validity based on certain criteria. The aim of this research is to increase students’ skills competency through exploring the nation’s historical values in short stories. This research is a qualitative research with descriptive methods with the subjects of this research being class students at SMA Negeri 6 Kota Serang in the odd semester. The results of the research that has been carried out show that the learning that educators have carried out has resulted in students gaining good or very good skill competencies. This cannot be separated from the treatment carried out by teachers, namely the selection of project-based learning models, the selection of varied methods, the use of learning technology, and the design of student-centred activities.